In search of Santa Claus: Samuelson, Stigler, and Coase theorem worlds - Steven G. Medema (Duke University, Center for the History of Political Economy (CHOPE), 2021)
One of the more striking features of the debate over the Coase theorem is the wide variety of models and theoretical frameworks used to discuss, evaluate, or otherwise analyze Coase's result - an artifact of an ambiguity in Coase's reasoning. Some framed Coase's result in a bargaining context and others in a competitive markets (both partial and general equilibrium) context. And players on both sides lined up with their demonstrations that the Coase theorem did or did not hold water. The parties involved in these debates, though, were often talking past each other, debating very different environments and models, and on different terms. Stabilization was elusive. Those who, like eight-year-old Virginia O'Hanlon in her famous letter asking if there is a Santa Claus, very much wanted to believe could certainly find reason to do so. For others, however, the theorem smacked more of the shopping mall Santa who reeks of alcohol and cigarettes.
Keywords: B2; B4; D62; H23; K00; 330; Coase theorem; Samuelson; Stigler; externalities; bargaining